Wakaf Goes Digital: Wakaf Innovation in Modern Era in Indonesia - Chesia Afriza; Ferri Andreansyah; Refi Yoanda Rahmatul Aulia; Riyan Adiputra (Journal of Islamic Digital Economic and Finance, 2025)
Introduction: The rapid development of information technology has driven digitalization across various aspects of life, including the management of waqf as an Islamic social finance instrument. In Indonesia, waqf management still faces challenges such as low waqf literacy, limited transparency, and lack of public participation, particularly among the millennial generation. Objective: This study aims to analyse the transformation of waqf through digital approaches and the role of millennials in supporting such innovations. Method: The research employs a qualitative literature review method, using the diffusion of innovation theory and social innovation in Islamic philanthropy to analyze secondary data from journals, reports, and digital waqf platforms. Result: The results show that digitalization of waqf through platforms such as Berkah Wakaf and Kitabisa.com has enhanced participation, efficiency, and transparency in waqf collection and distribution. However, challenges remain, including limited digital financial literacy and trust in digital platforms. These issues must be addressed through education, regulatory support, and cross-sector collaboration. Implication: With the right strategy, digital waqf has the potential to become a significant milestone in strengthening Islamic economics and empowering the ummah in the modern era